2017
DOI: 10.1088/2050-6120/aa5e31
|View full text |Cite
|
Sign up to set email alerts
|

Er3+-Tm3+-Yb3+:CaMoO4phosphor as an outstanding upconversion-based optical temperature sensor and optical heater

Abstract: Optical temperature sensing in Er-Tm-Ybcodoped CaMoO phosphor prepared by chemical co-precipitation route based on the near infrared (NIR) to green upconversion emission from Er ion is reported. The variation with respect to external temperature in emission intensity ratio of the green emissions around 530 nm and 552 nm, corresponding to the H → I and S → I transitions respectively, under 980 nm excitation has been studied in detail, to report the sensing property of the prepared material; the maximum sensor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Inorganic materials doped with RE 3+ (RE 3+ : rare earth) have structural disorders with a distribution of local cationic environments around the doping sites, which deviate from that of the ideal crystallographic positions. These materials attracted significant attention due to their novel structural characteristics and potential applications in various fields [34][35] . In particular, RE 3+ are added to the host matrices to enhance the luminescent properties 19,36 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inorganic materials doped with RE 3+ (RE 3+ : rare earth) have structural disorders with a distribution of local cationic environments around the doping sites, which deviate from that of the ideal crystallographic positions. These materials attracted significant attention due to their novel structural characteristics and potential applications in various fields [34][35] . In particular, RE 3+ are added to the host matrices to enhance the luminescent properties 19,36 .…”
Section: Introductionmentioning
confidence: 99%
“…These materials attracted significant attention due to their novel structural characteristics and potential applications in various fields. 34,35 In particular, RE 3+ are added to the host matrices to enhance the luminescent properties. 19,36 PL spectroscopy is a very efficient tool for the evaluation of the order−disorder effects in semiconductors, which leads to a better understanding of the structural changes that take place in materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pandey et al reported colour tunability in the Ho 3+ /Tm 3+ /Yb 3+ :Y 2 O 3 phosphors [22]. Dey et al reported that the Er 3+ -Tm 3+ -Yb 3+ :CaMoO 4 phosphor can be used as an outstanding UC based optical temperature sensor and optical heater [23]. The luminescence efficiency in the singly doped phosphors is very low; therefore a suitable sensitiser is needed to increase the luminescence efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of modern technology, rare earth (RE 3+ ) ions doped luminescent materials have evoked great attention because of their potential and practical applications in solid-state lighting, optical imaging, temperature sensors, color displays and so on [1][2][3][4]. Among numerous RE 3+ ions, Er 3+ ion is considered to be an excellent green emitting center in down-/up-conversion (DC/UC) luminescence materials thanks to its predominant ( 2 H11/2, 4 S3/2) → 4 I15/2 transitions [5].…”
Section: Introductionmentioning
confidence: 99%